Konsep Cinta dalam Tafsir Quran - Agam Royana; Muhammad Labibuddin (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2022)
This article presents the concept of love based on the perspective of Sheikh Mutawalli ash-Sya'rawi. Love is part of the perfection of a Muslim's faith, but there are still many things that do not reflect love in daily life. Within the family environment, domestic violence, abortion, neglection of children and parents often occur. In our society, we still see fraud, robbery, harassment and so on. Besode that, the tendency with personal interests tends to lead to apathy towards others. This happens because of the dim of love in the human heart, so the cure to minimize evil do is love itself. Therefore, we need to understand the nature of love and how to love that is in line with the Qur'an as a human guide. The discussion about love has been carried out by the Qur'an in various verses. Asy-Sya'rawi as a commentator, pays attention to the discussion of love in the verses of the Qur'an, and has an interesting view on it.